The Association Between Remnant Cholesterol and the Estimated 10-Year Risk of a First Hard Cardiovascular Event - Yang, Zhen; Yang, Kuo; Shi, Junhe; Yang, Qiaoning; Zhang, Ying; Gao, Jie; Shi, Dazhuo; Qu, Hua (Frontiers in Cardiovascular Medicine, 2022)
Background: Remnant cholesterol (Remnant-C), rather than TG, is believed to increase the risk of atherosclerotic cardiovascular disease. We evaluated whether Remnant-C is associated with estimated 10-year risk of a first hard atherosclerotic cardiovascular disease event. Methods: This cross-sectional study was performed on 2048 participants (1130 men and 918 women), aged 40 to 79 years, from the National Health and Nutrition Examination Survey (NHANES) 1999–2018. The independent variable was Remnant-C; the dependent variable was 10-year risk of a first hard atherosclerotic cardiovascular disease event (defined as nonfatal myocardial infarction or coronary heart disease death or stroke, over a 10-year period among people free from ASCVD at the beginning of the period). The other variables, such as smoking behavior, hypertension, diabetes etc., were considered as the potential effect modifiers. Multivariate linear regression models and smooth curve fittings were used to evaluate the association between Remnant-C and 10-year risk of a first hard atherosclerotic cardiovascular disease event. Subgroup analyses stratified by gender and race were also performed. Results: A positive association between Remnant-C and 10-year risk of a first hard atherosclerotic cardiovascular disease event was demonstrated in the fully adjusted model (β =0.078, [95%CI: 0.061–0.094], P < 0.001). The 10-year risk was increased by 0.078% for each 1mg/dl increase in Remnant-C. In the subgroup analysis for gender, this association was remained in both men (β=0.128, [95%CI: 0.108–0.148], P<0.001) and women (β=0.043, [95%CI: 0.016–0.070], P=0.00179). However, in the subgroup analysis for race, this association between Remnant-C and 10-year risk was also remained, but it reached at the inflection point at remnant-C 38 mg/dL, where the positive association did not become obvious for non-Hispanic Blacks population as other race. Conclusions: Remnant-C positively correlated with 10-year risk of a first hard atherosclerotic cardiovascular disease event.